Phân lập và đặc điểm của fucoidan từ năm loài rong mơ ở miền Trung - Nhứt, Nguyễn Duy; Lý, Bùi Minh; Cường, Nguyễn Mạnh; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
The comparative study of the content and structure characteristics of fucoidans from five Sargassum brown seaweed species in the south provinces of Vietnam was conducted. The yield of fucoidans was ca. 4% (w/w) based on dry seaweed. The percentage of sulfate and uronic acid content was determined by Scott method. Fucoidans were hydrolyzed with trifluoroacetic acid, acetylated and their L-fucose, D-xylose, D-rhamnose, D-mannose, D-glucose, and D-galactose contents were identified by gas chromatography. All polysaccharides isolated from Sargassum polycystum C. Agardh, S. mcclurei Setchell, S. swartzii (Turn.) C. Ag., S. oligocystum Mont. and S. denticarpum T. Ajisaka are high-sulfated L-fucoidans with sulfate content in range of 20 - 33%, and uronic acid content fluctuated from 14 to 23%. Fucose was the predominant monosaccharide in fucoidan from S. macclurei (ca. 51% total carbohydrates), while all four species S. polycystum, S. swartzii, S. oligocystum and S. denticarpum were enriched with both fucose (ca. 29 - 35%) and  galactose (26 - 33%).Keywords: Fucoidans, carbohydrates, sargassum, NMR, IR.